Design And Development Of Inventory Goods Application PT. Ditra Manunggal Jaya Sidoarjo - Eko Yudha Sadham Purnama; Tan Amelia; Siswo Martono (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. Ditra Manunggal Jaya (DMJ) is one of the companies that engaged in trading since 2004. DMJ has its headquarters and warehouse on Jalan Majapahit no 19, Sidoarjo. Currently PT. DMJ serves demand for various types of basic and supporting products such as rice, sugar, coffee, cooking oil, round wood, bamboo, animal feed, electronics and etc. Currently the process of determining the stock occurs some constraints that must looking for sales data in the form of documents or manual records and done recap sales one by one customer. Recording recap done using the help of Microsoft Excel software that requires 3-5 working days depending on the number of sales transactions that occur based on the problems that occur, given the proposed design goods inventory application by reorder point (ROP) method or purchase back. Application of the ROP method concerns the delivery time purchases from suppliers, so the stock value is guaranteed despite the process delivery of purchase is still running.